Efficacy Comparison of Low Level Laser Treatment with Muscle Energy Procedure Among Diabetic Patients Suffering from Frozen Shoulder: Laser versus Muscle Energy in Diabetic Frozen Shoulder - Qureshi, Abdul Samad; Hussain, Tanweer; Tunio, Muhammad Zaib; Aleem, Muhammad Arshad; Abideen, Zain Ul (Pakistan Journal of Health Sciences, 2024)
Frozen shoulder incidence in diabetic patient is twice as high as normal controls. There are various conventional as well as electrotherapies for its treatment within which low-level laser therapy versus muscle energy technique are well debated for efficacy in diabetic patients frozen shoulder. Objective: Comparative analysis of effectiveness of low-level laser therapy and muscle energy technique among diabetic patients with frozen shoulder. The study design was comparative study. The Place and Duration of Study was Department of Orthopaedic, Indus Medical College, Tando Muhammad Khan from 1st January 2023 to 30th June 2023. Methods: One hundred and twenty patients who were having diabetes mellitus (type 1 and type 2) and suffering from frozen shoulders were enrolled. The conventional therapeutic exercise included exercises like pendulum, arm overhead, finger wall ladder, twisting arm outwards, overhead pulley, cross-body reach exercises, hand behind-back exercise and outward rotation exercise. Muscle energy technique was administered in cases where restriction in shoulder flexion, as well as abduction, external rotation was observed. Results: There were 59% females and 41% males with majority being within the age group of 45-65 years. It was observed that there was a significant variance between pain scores at pretreatment and post treatment stages with highest value decrease observed in muscle energy technique group II. The ROM was least improved in control group only treated through conventional protocol. Conclusions: The Muscle energy technique is slightly more effective than low-level laser therapy technique in terms of pain, inflammation reduction and angular movements.